2012
DOI: 10.5039/agraria.v7i1a1489
|View full text |Cite
|
Sign up to set email alerts
|

Alternativas para o manejo integrado de fitonematoides em cana-de-açúcar

Abstract: RESUMOCom o objetivo de estudar produtos alternativos no manejo integrado de nematoides em cana-de-açúcar, foi instalado o experimento em blocos ao acaso, com cinco repetições, com os seguintes tratamentos, aplicados isoladamente ou em conjunto: Acibenzolar-S-Metil -ASM (100 g p.c./100 L) pulverizado aos dois e quatro meses após o plantio; fertilizante calcário (600 kg p.c. ha -1 ); extrato de nim a 1%; aldicarbe (10 kg p.c. ha -1 ); torta de filtro (50 t ha -1 ); ASM (100 g p.c./100 L) em rebolos; e testemunh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…Known as an important medicinal plant since the medieval period, neem has activity against more than 430 species of pests (Martinez, 2002) and is used for pest management due to the low cost and ecological viability; however, despite the effectiveness of neem by-products in the integrated management of pests and diseases (Chaves et al, 2012), there is little information on how these products affect soil chemical quality, particularly under semiarid conditions. This study aimed to evaluate variations in spatial-temporal distributions of soil chemical attributes after the incorporation of neem cake in a guava orchard in the Pernambuco semiarid region.…”
Section: Introductionmentioning
confidence: 99%
“…Known as an important medicinal plant since the medieval period, neem has activity against more than 430 species of pests (Martinez, 2002) and is used for pest management due to the low cost and ecological viability; however, despite the effectiveness of neem by-products in the integrated management of pests and diseases (Chaves et al, 2012), there is little information on how these products affect soil chemical quality, particularly under semiarid conditions. This study aimed to evaluate variations in spatial-temporal distributions of soil chemical attributes after the incorporation of neem cake in a guava orchard in the Pernambuco semiarid region.…”
Section: Introductionmentioning
confidence: 99%
“…The highest nematode concentration (9.3%) occurred at position −2 cm, with 111 individuals ( Figure 5B). Several studies have demonstrated the nematicide effect of neem and the efficiency in integrated plantparasitic nematode management (BARBOSA et al, 2010;CHAVES et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Rossetto & Dias (2005), a torta de filtro, quando incorporada ao solo em doses elevadas, apresenta propriedades corretivas da acidez do solo, devido aos efeitos quelantes da matéria orgânica sobre o alumínio. Chaves et al (2012) avaliando técnicas de manejo integrado no cultivo de cana-de-açúcar concluíram que os maiores aumentos de produtividade decorreram da utilização da torta de filtro e do fertilizante calcário, isoladamente e em conjunto.…”
Section: Introductionunclassified